Impact and Mitigation of Cyberattacks on IoT devices: A Lens on Smart Home - Demolinis, Remy (My University, 2023)
This Master's thesis, undertaken at the University of Turku in conjunction with an internship at Alten France, delves into the escalating issue of cyberattacks on IoT devices. This burgeoning area has begun to permeate various sectors of society, most notably through consumer products in smart homes. The primary motivations behind this chosen topic are the increased prevalence of IoT devices in our everyday lives and the corresponding surge in cyber threats, alongside the topic's real-world applicability to my work at Alten France, which is heavily invested in digital technology and innovation. The thesis begins with a comprehensive exploration of the current landscape of IoT cyber threats, including various attack vectors and their impact on different types of IoT devices. The challenges of securing IoT devices are then examined, highlighting the limitations and vulnerabilities of the IoT infrastructure. The research analyzes the impacts of cyberattacks on individual users, organizations, and society at large. It covers a wide range of consequences, such as privacy violations, financial losses, disruptions to critical infrastructure, and effects such as eroded trust in digital systems. The latter segment of the thesis addresses potential solutions and preventive measures to mitigate these impacts. The research does not aim to propose new strategies but seeks to inform future mitigation efforts based on its thorough analysis. On the whole, this thesis presents a meticulous and extensive examination of the impacts of cyberattacks on IoT devices, with an emphasis on smart homes. It underscores the urgent requirement for bolstered cybersecurity measures in our increasingly interconnected world, highlighting the severe repercussions of neglecting this need. By deepening the understanding of the extensive impacts of these cyberattacks, this research contributes valuable insights to academic discussions and supplies essential information for policymakers and industry professionals to develop more secure and resilient IoT systems.
Keywords: IoT, device, cyberattacks, impact, smart home, mitigation